Knowledge Sharing and Competitive Advantage in Public Universities: Mediating Role of Strategic Intent - Kashif Akram; Usman Ahmad (iRASD Journal of Management)
Public universities are the major source of higher education all over the world. Therefore, competitive public universities play a significant role in producing an effective labour force for society. The basic objective of the study is to examine the mediating role of strategic intent on the relationship between knowledge sharing and competitive advantage in the public higher education institutions (PHEIs) of Pakistan. Data were collected from the top management of the PHEIs of Pakistan by distributing the structured close-ended questionnaire. A total number of 192 questionnaires were received in a fully completed form that has been used for the final analysis. PLS-SEM was employed to examine measurement and structural model of the path model. The results reveal that KS is significantly and positively related to strategic intent and CA. Strategic intent also found to be significantly and positively related to CA. In addition, strategic intent mediates the relationship between KS and CA.